On Agarwal - Pang-type integral inequalities - Bencze, M.; Zhao, C. J (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We establish some new Agarwal – Pang-type inequalities involving second-order partial derivatives. Our results in special cases yield some of interrelated results and provide new estimates for inequalities of this type.